(untitled) (The Journal of Psychology and Sociology, 2018)
Social capital is an object of study of sociologists of postmodernism. In practice, leaders in the level of social capital development were called New Zealand, Switzerland and Sweden. This problem is not explored in Kazakhstan due to the fact that «social capital» is a relatively new concept, and at this stage it is considered the main prerogative of developed post-industrial states having developed civil society. The study of social capital is aimed at improving the basic conditions of socialization, determining the main vectors for the formation of a competitive nation, such as education, health, culture and social security. Confidential relations of social actors can be developed as a result of strengthening these aspects of the socialization of citizens. If in the studies of foreign scientists the conceptual foundations of social capital, the strategy of interaction of social groups, various models of civil society are clearly defined, then in Kazakhstan science there is an interest in studying this phenomenon, its conceptual designation in sociological knowledge, and the definition of the sociocultural model of civil society. In the scientific perspective, the sociological studies of foreign scientists on social capital contribute to the development of sociological science in Kazakhstan. In economic terms, social capital expands the information space for labor market subjects, contributes to the creation of civilized market relations; in the social plan promotes formation of a civil identity and a civil society; will lead to the expansion of trust relations and develops social cooperation. The goal is to study the basic conceptual approaches to the study of social capital, the disclosure of the potential of social capital as a new resource for modernizing society. The tasks of the problem are closely connected with the analysis of the content of methodological approaches and the definition of their attitude to them, as well as the rationale for the resource potential of social capital. The grouping of conceptual approaches to the study of social capital by types of definitions will be the main result of the study. Key words: modernization, social capital, trust, solidarity, civil socialization, group identity.